PENERAPAN MODEL PEMBELAJARAN QUANTUM LEARNING PADA MATA PELAJARAN IPA DI KELAS IV MI NEGERI 3 LAMPUNG BARAT - Irawan, Dedi; Mutmainah, Tika Rina; Yulia, Liyan Desi (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
This research is motivated by the low learning outcomes in science lessons for fourth grade students of MI Negeri 3 West Lampung. One of the contributing factors is the teacher who lectures more in delivering material, so that students become bored quickly and their science learning becomes less than optimal. The purpose of this study was to determine the application of Quantum Learning Models in MI Negeri 3 West Lampung. The research method used in this study is descriptive qualitative research. Data collection techniques used were interview, observation and documentation techniques. Data analysis techniques in this study are Miles and Huberman models, namely 1) data collection; 2) data reduction; 3) display data; 4) draw conclusions. Based on the results of the study, it was found that the application of the quantum learning model in MIN 3 West Lampung went well. The implementation of learning activities is based on the quantum learning model which consists of six learning stages, namely: growing, natural, naming, demonstrating, repeating, and celebrating which is then known as TANDUR. The teacher is able to apply this method in accordance with the steps that exist, although in reality the teacher experiences obstacles in class conditioning during the discussion activities but the teacher is able to solve the problem well. Based on the results of the study it can be concluded that the application of the quantum learning model in MIN 3 West Lampung went well.